2014
DOI: 10.1177/0269215514545350
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes following preoperative inspiratory muscle training in patients undergoing cardiothoracic or upper abdominal surgery: a systematic review and meta analysis

Abstract: Preoperative inspiratory muscle training significantly improves respiratory (muscle) function in the early postoperative period, halving the risk of pulmonary complications. The training does not increase length of stay, but more data are required to confirm whether it reduces length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 36 publications
5
72
0
1
Order By: Relevance
“…A recent systematic review also confirmed a 50% reduction in PCC in patients undergoing cardiothoracic and upper abdominal surgery who completed preoperative respiratory muscle training programs. It is thought that respiratory muscle weakness contributes to PCC [24]. …”
Section: Preoperative Lung Protective Strategiesmentioning
confidence: 99%
“…A recent systematic review also confirmed a 50% reduction in PCC in patients undergoing cardiothoracic and upper abdominal surgery who completed preoperative respiratory muscle training programs. It is thought that respiratory muscle weakness contributes to PCC [24]. …”
Section: Preoperative Lung Protective Strategiesmentioning
confidence: 99%
“…Inspiratory muscle training (IMT), a training modality aimed at increasing strength and endurance of the inspiratory muscles, can increase ventilatory capacity. Systematic reviews of patients undergoing cardiac and upper abdominal surgery have shown that preoperative IMT can decrease the rate of postoperative pneumonia. Whether preoperative IMT is of benefit in patients undergoing oesophagectomy is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…2 Risk factors for PPCs are: duration of anaesthesia, surgical category, current smoking, respiratory comorbidity, and predicted maximal oxygen uptake. 3 Preoperative physiotherapy interventions, 4 particularly inspiratory muscle training, 5 decrease the risk of PPCs. Postoperatively, early mobilisation is recommended to minimise PPCs.…”
Section: Introductionmentioning
confidence: 99%